Application of Social Media Threads in College Libraries - Saputra, Ricco Herdiyan; Waziana, Winia (UIN Raden Intan Lampung, 2023)
The development of information technology has brought significant changes in various sectors, including university libraries. Social media, as one of the information technology innovations, has become an effective tool in expanding access and improving library services. This research focuses on the application of social media